Predictive Values of Handgrip Strength for Protein-Energy Wasting Among Patients Undergoing Maintenance Hemodialysis: A Systematic Review and Meta-Analysis - Muhammad Haneef Ghifari; Seba Talat Al-Gunaid; Derren David Christian Homenta Rampengan; Juan Fransiscus Wira; Maimun Syukri; Amanda Yufika; Muhammad Habiburrahman; Muhammad Iqhrammullah (Kidney and Dialysis, 2025)
Protein-energy wasting (PEW) increases the morbidity and mortality in maintenance hemodialysis (MHD) patients. The existing screening tools (e.g., Malnutrition-Inflammation Score (MIS)) are time-consuming and require expertise. Consequently, assessing a more practical and reliable tool such as handgrip strength (HGS) is important, as it strongly correlates with the PEW status in patients undergoing MHD, in whom increased protein and fat breakdown leads to muscle strength and function loss. A systematic search of five databases identified studies assessing HGS’s predictive value for PEW in patients undergoing MHD, using MIS as the reference. The quality of the studies was evaluated with the updated QUADAS tool. A diagnostic meta-analysis was carried out to estimate the pooled sensitivity, specificity, sROC, and sAUC using a two-level mixed-effects model. From 350 records, five studies were obtained which were included for analysis. The pooled sensitivity and specificity of the HGS among male patients were 68% (95%CI: 63–73%) and 66% (95%CI: 53–77%), respectively. Among female patients, the pooled sensitivity and specificity were 73% (95%CI: 62–82%) and 65% (95%CI: 48–79%), respectively. The positive likelihood ratio and negative likelihood ratio for male patients were 2.0 (95%CI: 1.4 to 2.9) and 0.48 (95%CI: 0.38 to 0.60), respectively. Meanwhile, among female patients, the positive likelihood ratio and negative likelihood ratio were 2.1 (95%CI: 1.4–3.1) and 0.41 (95%CI: 0.29–0.59), respectively. The sAUC for males and females was estimated to be 0.69 (95%CI: 0.65 to 0.73) and 0.75 (95%CI: 0.71–0.79). In summary, the sensitivity and specificity of the HGS were modest for all sexes, with females being more sensitive. HGS may be useful for triaging during daily screening and guiding further examination, but it requires supporting measurements to be employed as a diagnostic tool. PROSPERO: CRD42024595677 as of 1 October 2024.